Hematological and Histological Analysis of Tilapia (Oreochromis Niloticus) Cultured in Floating Net Cages After Disease Outbreak - Ririen Kartika Rini; Siti Aisiah; Olga; Lutfia Nafisah (Jurnal Penelitian Pendidikan IPA, 2024)
Recently, Tilapia fish cultivated in floating net cages in Karang Intan District experienced a sudden death from June 4 to June 5. At some point, mortality reached 50% of the population in floating net cages. The purpose of this study was to analyze the hemtology and histology of tilapia (Oreochromis niloticus) after exposure to disease outbreaks that were cultivated in floating net cages. The research location was carried out at the Laboratory of Fish Pests and Diseases, Faculty of Fisheries and Maritime Affairs, University of Lambung Mangkurat. The animal samples used were tilapia showing clinical symptoms of sick fish obtained from floating net cages in Mali-Mali Village, Karang Intan District, which experienced quite high fish mortality cases and 3 fish were taken. Based on the results of hemtological analysis of tilapia (Oreochromis niloticus) after being exposed to disease outbreaks which were cultivated in floating net cages, the hemoglobin levels of tilapia obtained in this study ranged from 6.9-7.8 g/dl, the average hematocrit of tilapia was obtained in this study has a range between 37.2 - 58.9%, the average tilapia leukocrit obtained in this study has a range between 2.89 - 6.61% and blood plasma is a liquid component of blood consisting of 99% water and 8-9% protein.